PMMA-LiBOB gel electrolyte for application in lithium ion batteries - Kufian, M.Z.; Aziz, M.F.; Shukur, M.F.; Rahim, A.S.; Ariffin, N.E.; Shuhaimi, N.E.A.; Majid, S.R.; Yahya, Rosiyah; Arof, Abdul Kariem (Elsevier, 2012)
Different amounts of lithium bis(oxalato) borate (LiBOB) have been added into a mixture of equal weights of ethylene carbonate (EC) and propylene carbonate (PC). The variation of molar conductivity of the LiBOB based liquid electrolyte with square root of salt concentration obeys the weak electrolyte theory. The 0.6 M LiBOB in EC/PC liquid electrolyte with highest room temperature conductivity of 4.8 mS cm - 1 was chosen for further work. 10 to 50 wt. PMMA was added to this composition and heated between 343 and 353 K for 20 min to obtain the gel polymer electrolytes (GPEs). Due to its dry state and flexibility the GPE with 20 wt. PMMA was further investigated by electrochemical impedance spectroscopy (EIS), differential scanning calorimetry (DSC), transference number measurement, linear sweep voltammetry (LSV) and cyclic voltammetry (CV). The GPE was used as an electrolyte in a Li/LiCoO 2 cell, and subjected to charge-discharge cycling between 4.2 and 3 V. The ionic conductivity of the 20 wt. PMMA containing GPE is 3.58 mS cm - 1 at 373 K. Conductivity-temperature relationship obeys Vogel-Tammann-Fulcher (VTF) equation. The glass transition temperature, T g of the GPE is 298 K. Lithium ion transference number obtained is 0.46 at 298 K. The GPE shows stability up to 4.7 V versus Li/Li +. The discharge capacity is stable over 20 cycles at â¼ 130 mA h g - 1.